A splitting preconditioner for the incompressible navier–stokes equations - Hu, Ze-Jun; Huang, Ting-Zhu; Tan, Ning-Bo (Mathematical Modelling and Analysis, 2013)
In this paper, a splitting preconditioner based on the relaxed dimensional factorization (RDF) preconditioner and the modified augmented Lagrangian (MAL) preconditioner for the incompressible Navier–Stokes equations is presented. The preconditioned matrix is analyzed, and similar results arising from the RDF and the MAL preconditioners are obtained. The corresponding details of the spectrum analysis are given. Finally, we compare the three preconditioners and numerical experiments are implemented by using the IFISS package.